The involvement of attentional biases in endogenous pain inhibition and autonomic reactivity - Einav Gozansky; Irit Weissman-Fogel; Hadas Okon-Singer (PLoS ONE, 2026)
Background Attention is a key factor in shaping pain perception and modulation, yet its role in explaining individual differences in endogenous pain inhibition—commonly assessed in humans using conditioned pain modulation (CPM)—remains poorly understood. While studies show that attentional focus during dual pain stimulation can influence CPM efficacy, the contribution of attentional biases has not been examined. In addition, although psychological traits and autonomic nervous system activity have both been linked to CPM, their relative contributions to individual variability remain unclear. The present study examined whether attentional biases predict individual differences in pain sensitivity and endogenous pain modulation, and whether psychological, emotional, and autonomic factors are associated with these outcomes. Methods Eighty-six healthy women completed psychological questionnaires assessing anxiety, depression, and fear of pain. They also performed two modified attentional bias tasks: a novel perceptual load task and a dot-probe task. Quantitative sensory testing included pain ratings of suprathreshold tonic heat pain alone and under conditioning (CPM paradigm). Heart rate (HR) was measured at baseline, during, and after both test-stimulus alone and under conditioning. Results Greater interference from pain-related cues under high perceptual load was linked to increased pain sensitivity, whereas greater attentional avoidance in the dot-probe task was associated with higher fear of pain. In contrast, none of the examined factors predicted CPM magnitude. HR increased during the test-stimulus under conditioning and remained elevated in recovery. Exploratory analyses further showed that higher emotional distress was related to blunted HR during test-stimulus under conditioning, and that both perceptual load interference and attentional avoidance predicted elevated HR during recovery. Conclusions Attentional biases to pain predicted pain sensitivity beyond psychological and autonomic influences. Although unrelated to CPM, they were associated with HR dynamics, suggesting a role in autonomic regulation during pain and recovery.